COMMENTS IN FACEBOOK ABOUT OPPOSITE MEANINGS ON PRESIDENTIAL DEBATE (KOMENTAR DI FACEBOOK MENGENAI OPOSISI MAKNA DALAM DEBAT PRESIDEN) - Sariah Sariah (Metalingua: Jurnal Penelitian Bahasa, 2020)
The opposition of meaning is part of the semantic relation which shows the existence of a meaningful relation or semantic relation between a word or another language unit in a text. This paper tries to scrutinize what types of the meaning opposition are used and how they create the image of the president and vice president candidates. The purpose of this paper is to reveal the word or phrase that is in opposition of meaning and its type as well as the images of president and vice president candidates being presented on Facebook. This study uses descriptive methods to describe the types and meanings and images of president and vice president candidates. The data were gained in the form of language elements such as opposing words and groups of words. They were collected from the comments on the first presidential and vicepresidential debate on Facebook from 17-31 January 2019. The result shows that the opposition found on the debate consists of absolute opposition, polar opposition, relational opposition, and hierarchical opposition bound by cohesion tools to connectthe semantical relations or coherence. The meanings obtained are those which contain elements of irony, insults, reproach which ultimately denigrates and overthrows the president and vice president candidates.AbstrakOposisi makna adalah bagian dari relasi makna yang menunjukkan adanya hubungan kemaknaan atau relasi semantik antara sebuah kata atau satuan bahasa yang lain dalam suatu teks. Masalah yang menjadi fokus tulisan ini adalah bagaimana jenis dan makna oposisi yang digunakan dan bagaimana makna oposisi tersebut membangun citraan pasangan calon capres dan cawapres. Tujuan tulisan ini adalah mengungkapkan jenis dan makna oposisi serta citraan capres dan cawapres di media sosial Facebook. Penelitian ini menggunakan metode deskriptif untuk memaparkan jenis dan makna serta citraan capres dan cawapres. Data penelitian berupa unsur lingual berupa kata dan kelompok kata yang beroposisi. Sumber datanya adalah komentar pada Debat I Capres dan Cawapres di media sosial Facebook dari tanggal 17—31 Januari 2019. Temuannya adalah oposisi Debat I Capres dan Cawapres terdiri atas oposisi mutlak, oposisi kutub, oposisi hubungan, dan oposisi hierarki yang diikat oleh alat kohesi untuk menghubungkan jaringan makna atau koherensi. Makna yang diperoleh adalah makna-makna yang mengandung unsur ironi, hinaan, dan celaan yang ujungnya adalah merendahkan serta menjatuhkan pasangan calon presiden dan wakil presiden.